Cognitive-developmental approach to coaching: an interview with Robert Kegan - Bachkirova, Tatiana (Coaching : an international journal of theory, research & practice, 2009)
Dear Bob, Your work on the evolution of consciousness and its implications for supporting adult learning and professional development is very important for coaching. I believe that most coaches hold dear to their heart the idea of the possibility and necessity of ongoing psychological transformation in adulthood and the need for a better fit between adult capacities and the hidden demands of modern life. It is not surprising then that your approach to understanding adult development, well known as a meaningful and coherent theory, now is in the process of creating its own niche in coaching practice. I would like this process to be the focus of our interview.